PELAKSANAAN HAK ASUH BERSAMA TERHADAP ANAK DI BAWAH UMUR : ANALISIS NORMA HUKUM - Meliani, Meliani; Jaya, Indra Budi (Fakultas Agama Islam Universitas Muhammadiyah Bandung, 2022)
Regarding child custody after divorce, Indonesia adheres to a sole custody system with reference to the Compilation of Islamic Law. However, in recent years the Religious Courts have implemented a shared custody system which refers to the Marriage Law and the Child Protection Act as considerations by taking into account the best interests of the child. This paper tries to examine comparatively the legal basis governing joint custody rights for minors. The method used in this research is a qualitative research with a normative juridical approach which is described in an analytical descriptive manner. In this paper, the hierarchical theory of laws and regulations is used, namely the laws and regulations set by the state, so the lower provisions must not conflict with the higher provisions. The results of this study indicate that the concepts used in the implementation of the joint custody system in Indonesia are the concept of physical custody division and the concept of legal custody sharing, with the pattern of distribution of residence time determined by the judge in the Court without prejudice to the value of the best interests of the child. This is a form of transformation of childcare laws that were previously applicable in Indonesia. After a comparison was made on the legal norms governing joint custody of minors, it was found that every statutory regulation governing child custody places legal subjects differently so that it has implications for their legal position. keyword: children, legal custody, Sharing custody system